Isolating mechanisms as sustainability factors of resource-based competitive advantage = Mechanizmy izolacji jako czynnik trwałości zasobowej przewagi konkurencyjnej. Studium przypadku - Mazur, Karolina; Kulczyk, Zdzisław (Zielona Góra: Faculty of Economics and Management Press)
Strategic resources which fulfill conditions of VRIN generate extraordinary profits for organizations. The possibility of these long-term profits (rents) to achieve can be protected by isolating mechanisms. These mechanisms can be different but the most important are causal ambiguity, lead time, path dependency, the role of history, socially complex links and the time compression diseconomies. These mechanism can be WIM and AIM type (based on willingness or ability). They can be also analyzed on individual, organizational or social levels. The article presents the case study which supports available systems of mechanism categorization.
Keywords: ujęcie zasobowe; mechanizmy izolacji; trwała przewaga konkurencyjna; małe przedsiębiorstwo; Resource Based View; isolating mechanisms; sustainable competitive advantage; small business